Recent advances in PEDOT:PSS integrated graphene and MXene-based composites for electrochemical supercapacitor applications - Faruk, Omar (2023)
Considering the power consumption by the electronics of the future, it is important to design state-of-the-art energy storage devices with flexible and lightweight structures, which would enable the devices to operate uninterruptedly for a longer time. Supercapacitors (SC), a hybrid type of energy storage device, have gained much attention from the scientific community, compared to their counterparts (batteries and capacitors) because of their high energy and power output to power up devices, mostly for flexible electronics. In addition, the recent breakthrough in materials chemistry research, mainly the invention of novel 2D materials such as graphene and MXene opens a wide window for more research in SC because of their inspiring properties compared to other nanomaterials. Consequently, these 2D nanomaterials have been extensively studied to integrate with other materials like intrinsic conducting polymers (ICP) to improve the performance of fabricated energy storage devices. Among different ICPs, commercially successful PEDOT:PSS is one of the materials that have been integrated with both the graphene and MXene to boost up the capacitive behaviors of the SC by taking advantage of ICP and 2D nanomaterials. As a result, a huge success (in terms of lab scale materials design as well as device performance) has been seen in the last decade, although there is still room for developing SC for next-generation applications. Thus, this article has summarized the recent advancement of electrochemical supercapacitors constructed by incorporating PEDOT:PSS with graphene and MXene.